2020
DOI: 10.26434/chemrxiv.12251171.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Synthesis of Novel Selenocyanates and Evaluation of Their Effect in Cultured Mouse Neurons Submitted to Oxidative Stress

Abstract: <p>Herein we report the synthesis of novel selenocyanates and assessment of their effect on the oxidative challenge elicited by hydrogen peroxide (H<sub>2</sub>O<sub>2</sub>) in cultured mouse neurons. First, <i>α</i>-methylene-<i>β</i>-hydroxy esters were prepared as precursors of allylic bromides. A reaction involving the generated bromides and sodium selenocyanate was conducted to produce the desired selenocyanates (<b>3a-f</b>). We next prep… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 55 publications
0
6
0
Order By: Relevance
“…In 2020, Frizon et al reported a series of allylic selenocyanates, such as compounds 14−16, and evaluated for their antioxidant activities in cultured mouse neurons under oxidative stress induced by H 2 O 2 . 20 Interestingly, compounds 14−16 exhibited significant antioxidant activities comparable to that of diphenyl diselenide (Ph 2 Se 2 ). While a significant number of neutral antioxidant organoselenium compounds are reported in the literature as synthetic mimics of GPx, examples of ionic organoselenium compounds as antioxidants are relatively limited.…”
Section: ■ Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In 2020, Frizon et al reported a series of allylic selenocyanates, such as compounds 14−16, and evaluated for their antioxidant activities in cultured mouse neurons under oxidative stress induced by H 2 O 2 . 20 Interestingly, compounds 14−16 exhibited significant antioxidant activities comparable to that of diphenyl diselenide (Ph 2 Se 2 ). While a significant number of neutral antioxidant organoselenium compounds are reported in the literature as synthetic mimics of GPx, examples of ionic organoselenium compounds as antioxidants are relatively limited.…”
Section: ■ Introductionmentioning
confidence: 99%
“…23 In 2014, Stoyanovsky et al reported the synthesis of cationic ebselen derivative 19 as a mitochondria-targeting GPx mimic with potential as a radiation mitigator. 24 In 2020, Arsenyan and coworkers have reported another ionic mitochondria-targeting fused isoselenazolium chloride (20), which exhibited potent anticancer activities toward breast cancer cells via elevation of the intracellular ROS level. 25 Herein, we report the first examples of benzimidazole-and imidazole-based ionic organoselenium compounds such as benzimidazole-and imidazolebased selenazolium selenocyanates (21a, 21b, 22a, and 22b), selenazinium selenocyanates (21c, 21d, 22c, and 22d) and the corresponding open-chain selenocyanates (21e, 21f, 22e, and 22f) as GPx mimics (Figure 2).…”
Section: ■ Introductionmentioning
confidence: 99%
“…These methodologies generally require high-cost equipment, result in low yield, and use toxic solvents, which reduces the sustainability of the process. In line with our interest in discovering and developing a new sustainable, efficient methodologies for biologically active compounds and patient-compliant alternative for leishmaniasis treatment [10][11][12][13][14][15][16][17], our research group aimed to yield natural-based bioactive compounds with multitarget properties. To achieve this purpose, we designed a scalable, easy-to-replicate, and inexpensive synthetic route to obtain flavonol and chalcone analogs.…”
Section: Of 23mentioning
confidence: 99%
“…As part of our research interest in synthesis and biological evaluation of heterocyclic compounds [19][20][21][22][23][24][25][26][27][28], herein we report the antimicrobial and antibiofilm activities, of two 4,5-dihydro-1H-pyrazole-1-carboximidamide hydrochlorides ((trifluoromethyl) phenyl-substituted and bromophenyl-substituted), against four pathogenic Salmonella spp. serotypes.…”
Section: Introductionmentioning
confidence: 99%